University of Kansas sustainable automotive engineering - Depcik, Christopher (Kansas State University, 2011)
University of Kansas (KU) students, who refer to themselves as the EcoHawks, apply engineering techniques in order to solve real-world problems by approaching the situation from five vectors of success: education, energy, environment, economics and ethics. Each of these concepts individually addresses specific aspects of sustainability, shaped by the confluence of the ideals of people, planet and prosperity. It is through this multi-leveled application that the students develop the means to face the challenges of a sustainable approach to automobiles and the energy infrastructure. This presentation will discuss how the following efforts include a practical approach to sustainability for current and future national needs in this area. To date, the students have recycled a 1974 VW Super Beetle that had been sitting on a car lot for over two years and turned it into a plug-in series hybrid vehicle powered by lead-acid batteries and a diesel generator that runs on 100% biodiesel created from the used cooking oil on campus. In addition, students built a solar energy filling station on campus that allows recharging of the Beetle battery pack in a little over half a sunny day. Current efforts focus on integrating wind energy into the facility while renovating a 1997 GMC Jimmy into a modern Electric Vehicle (AC three-phase motor and LiFePO4 batteries) for use by KU Libraries on campus. Moreover, students have been able to explore advanced technologies on the small scale adding to the future capabilities of the project. This is evident by the student’s unique Remote Control car builds involving fuel cell and parallel hybrid vehicles and their smart grid demonstration project in progress. Finally, the students actively integrate K-12 education in their efforts through Engineering Exposition and work interdisciplinary with other KU peers.
Keywords: Automotive engineering; Hybrid vehicles; Biofuels; Electric vehicles; University of Kansas; EcoHawks